Answers

2014-02-12T23:41:59+01:00
5x + 3y = 9.   ...... Equation 1
5x - 4y = 6 ...... Equation 2 
0 -y = 3 
D.b.s by -y 
y = -3 

Substitute y=-3 in eqn 1
5x+3y=9
5x +3 (-3) = 9
5x -9 = 9 
collect like terms
5x = 9-9 
5x = 0
D.b.s by 5 
x = 0 / 5 
therefore x = 0 


then you substitute 

EXPLANATION 
if you look at the equation 5x and 5x are the same and the law says when the numbers have the same positive sign you subtract. When you finish subtracting you will get -y = 3 you divide both side by -1 your answer will be -3.

after that you substitute it means that whenever you see y in equation 1 put -3 
1 5 1